AIRE is not essential for the induction of human tolerogenic dendritic cells. (18th May 2016) - Crossland, Katherine L.; Abinun, Mario; Arkwright, Peter D.; Cheetham, Timothy D.; Pearce, Simon H.; Hilkens, Catharien M. U.; Lilic, Desa
Abstract: Loss-of-function mutations of the Autoimmune Regulator ( AIRE ) gene results in organ-specific autoimmunity and disease Autoimmune Polyendocrinopathy type 1 (APS1)/Autoimmune Polyendocrinopathy Candidiasis Ectodermal Dystrophy (APECED). The AIRE protein is crucial in the induction of central tolerance, promoting ectopic expression of tissue-specific antigens in medullary thymic epithelial cells and enabling removal of self-reactive T-cells. AIRE expression has recently been detected in myeloid dendritic cells (DC), suggesting AIRE may have a significant role in peripheral tolerance. DC stimulation of T-cells is critical in determining the initiation or lack of an immune response, depending on the pattern of costimulation and cytokine production by DCs, defining immunogenic/inflammatory (inflDC) and tolerogenic (tolDC) DC. In AIRE-deficient patients and healthy controls, we validated the role of AIRE in the generation and function of monocyte-derived inflDC and tolDCs by determining mRNA and protein expression of AIRE and comparing activation markers (HLA-DR/DP/DQ, CD83, CD86, CD274(PDL-1), TLR-2), cytokine production (IL-12p70, IL-10, IL-6, TNF-α, IFN-γ) and T-cell stimulatory capacity (mixed lymphocyte reaction) of AIRE+ and AIRE- DCs. We show for the first time that: (1) tolDCs from healthy individuals express AIRE; (2) AIRE expression is not significantly higher in tolDC compared to inflDC; (3) tolDC can be generated from APECED patient monocytes and (4) tolDCs lacking AIRE retain the same phenotype and reduced T-cell stimulatory function. Our findings suggest that AIRE does not have a role in the induction and function of monocyte-derived tolerogenic DC in humans, but these findings do not exclude a role for AIRE in peripheral tolerance mediated by other cell types.